2018
DOI: 10.1002/pds.4554
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and antipsychotic medication errors reported to United States poison control centers

Abstract: This study provides a comprehensive overview of non-health care facility unintentional therapeutic errors associated with antidepressant and antipsychotic medications. The frequency and rate of these errors increased significantly from 2000 to 2012. Given that use of these medications is increasing in the US, this study provides important information about the epidemiology of the associated medication errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…13 Based on the National Poison Data System in the United States from 2000 to 2012, Kamboj et al found that atypical antipsychotics-a group of psycholeptics were associated with 32.1% of medication errors among children aged 6 to 19 years, compared with 20.6% among adults aged 20 years or above. 44 Our results thus join the emerging literature in suggesting a pediatric-specific pattern concerning medication errors involving psycholeptics. Finding effective targeted strategies for reducing pertaining medication errors and associated harm is crucial.…”
Section: 41supporting
confidence: 80%
“…13 Based on the National Poison Data System in the United States from 2000 to 2012, Kamboj et al found that atypical antipsychotics-a group of psycholeptics were associated with 32.1% of medication errors among children aged 6 to 19 years, compared with 20.6% among adults aged 20 years or above. 44 Our results thus join the emerging literature in suggesting a pediatric-specific pattern concerning medication errors involving psycholeptics. Finding effective targeted strategies for reducing pertaining medication errors and associated harm is crucial.…”
Section: 41supporting
confidence: 80%